Combination of Radiofrequency Ablation With Resiquimod to Treat Hepatocellular Carcinoma Via Inflammation of Tumor Immune Microenvironment and Suppression of Angiogenesis - Tian, Zhou; Hong, Baojian; Chen, Jianzhong; Tang, Zhe (Frontiers in Oncology, 2022)
Background: Radiofrequency ablation (RFA) destroy tumors through hyperthermic injury, which induce the release of immunogenic intracellular substrates and damage associated molecular patterns (DAMPs) to evoke a systemic immune response, but its therapeutic effect is limited. This study aimed to combine RFA with an immunomodulator, Resiquimod (R848), to enhance RFA-induced antitumor immunity. Methods: We performed RFA on subcutaneous tumors in immunocompetent mice and intraperitoneally injected R848 to observe the efficacy of the combination therapy. Our research investigated changes in the composition of tumor-infiltrating immune cells in primary and distant tumor by flow cytometry. Natural killer (NK) cell depletion experiment was applied to confirm the role of NK cell in combination therapy. The expression levels of cytokines and chemokines were detected by real-time quantitative PCR. Immunohistochemical test was conducted to reveal tumor angiogenesis, tumor proliferation and apoptosis after different treatments. Results and conclusion: Compared with RFA or R848 monotherapy, combination therapy significantly slowed tumor growth, prolonged survival time, and shrank tumor-draining lymph nodes of tumor-bearing mouse. Flow cytometry results showed that tumor-infiltrating immune cells, total T cells, the ratio of CD8+ T and NK cells to CD45+ cells, and functional NK cells were obviously increased after combined treatment. Distal tumor growth was also suppressed, the profile of tumor-infiltrating immune cells was remodeled too. In addition, the additive effect of combination therapy disappeared after NK cell depletion. Furthermore, immunohistochemical results verified that R848 inhibited tumor angiogenesis in murine liver cancer, and the combination therapy promoted tumor cell apoptosis. In conclusion, our data suggesting that RFA combined with R848 stimulated a stronger antitumor immune response and effectively inhibited liver cancer progression in a NK cell-dependent manner. Meanwhile, we confirmed that R848 inhibited tumor angiogenesis and promoted apoptosis in murine liver cancer. Overall, this is a promising therapeutic strategy to improve the efficacy of RFA in the treatment of liver cancer, and provides a novel option for combined thermal ablation and immunotherapy.